Analisis Motivasi dan Beban Kerja Karyawan terhadap Kepuasan Kerja Karyawan pada PT Bali Kulina Utama (Indoguna Bali) - Cahyani, Putu Yunita Intan; Putra, Kadek Dwi Cahaya; Narti, Ni Ketut (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The aim of this research is to analyze how much influence motivation and workload have on employee job satisfaction at PT Bali Kulina Utama (Indoguna Bali). This research is a descriptive statistical analysis research that uses a research sample of 97 people. To collect data in this research, a questionnaire was distributed via social media. In this research, a simple random sampling method was used. The analysis technique used is multiple linear regression analysis which is then processed and analyzed using the SPSS version 26 program. The results of this study show that motivation partially has a positive and significant effect on job satisfaction with a coefficient value of 5.926 with a significant value of 0.000, partial workload has no positive and significant effect with a coefficient value of -1.082 and a significant value of 0.282. Motivation and workload simultaneously have a positive and significant effect on job satisfaction with an F count of 18.237 > 3.09 and a significance value of 0.000 < 0.05 with a coefficient of determination of 28%.